فعالية تطبيق طريقة شرفة داخلية الإجتماعية فى تعليم اللغة العربية لترقية مهارة الكلام بمدرسة المتوسطة الإسلاميّة منبع العلوم بانداءن باسوروان - Zainuddin Zainuddin; Nur Rokhmatulloh (Universitas Yudharta Pasuruan, 2019)
Islamic Junior High Manbaul Ulum Pandaan Pasuruan is one of the Islamic Junior High school in Pasuruan that use Arabic language learning with teaching media. Models and teaching methods used are a combination method. The approach used by the researchers in this study is the quantitative approach. The type of study is a post-test instruments in one sample (posttest in one group). The results showed teachers use various methods that vary in the use of Methods Season Gallery is that: rote methods, methods silent way, the method of reading, teaching methods friend, while the media used are films, motion pictures, still pictures. The result of the test was 23% and 40% value A value B in the aspect of speakiing meanings synchronize with the image, value A 25%, value B 16% and 41% of their value C. aspect know the meaning. Incorporation of the results and the methods used to say this media learning using Methods Season Gallery is effective in increasing Advanced speaking as seen from the results of the percentage of students above received value was up.